BRUCELLOSIS IDENTIFICATION ON FARMERS IN PINRANG DISTRICT (Nusantara Medical Science Journal, 2017)
ABSTRACT Introduction : Brucellosis is one of twenty-two types of Strategic Animal Diseases (PHMS) that are zoonotic, (i.e., spreadable from animals to humans according to the Decree of The Minister of Agriculture no.   4026  / Kpts. / OT.140  / 3/2013). This study aims to investigate brucellosis transmission on the  cattle farmers in Pinrang. Serological diagnosis suggests the possibility of brucellosis-infected cattle farmers in Pinrang based on Rose Bengal Test (RBT) and  Complement Fixation Test (CFT). Methods : This research was conducted by taking  blood  serum from  42  cattle  farmers,  which  then  analyzed  using  the  Rose Bengal Test (RBT) and  Complement Fixation Test (CFT). Results : Rose Bengal Test (RBT) and Complement Fixation Test (CFT) results showed brucellosis positive on 2 cattle farmer’s samples of Lembang and  Dumpanua subdistrict in Pinrang disctrict with age  47  and  53 years old. Conclusion : There  were brucellosis cases on cattle farmers in Pinrang district. Keywords: Brucellosis, CFT ,RBT